2016
DOI: 10.1002/ijc.29967
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in cancer survival: Impact of tumour stage, socioeconomic status, comorbidity and type of treatment in Norway

Abstract: Cancer survival varies by place of residence, but it remains uncertain whether this reflects differences in tumour, patient and treatment characteristics (including tumour stage, indicators of socioeconomic status (SES), comorbidity and information on received surgery and radiotherapy) or possibly regional differences in the quality of delivered health care. National population-based data from the Cancer Registry of Norway were used to identify cancer patients diagnosed in 2002-2011 (n 5 258,675). We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
3
28
0
1
Order By: Relevance
“…population‐based registries data, ecological deprivation index, net survival) also showed lower survival among patients living in the most deprived environments compared to those living in the least deprived ones, for most cancer sites . More broadly, all studies investigating social inequalities in cancer survival worldwide have reported lower survival among the most deprived for a large majority of cancer sites, with no significant inverse association . Our findings are therefore supported by those from the literature, and bring new information about the situation in France and the impact of social deprivation on cancer survival for cancer sites with mitigated results in the literature (such as stomach, ovary, melanoma, thyroid, CNS or pancreas).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…population‐based registries data, ecological deprivation index, net survival) also showed lower survival among patients living in the most deprived environments compared to those living in the least deprived ones, for most cancer sites . More broadly, all studies investigating social inequalities in cancer survival worldwide have reported lower survival among the most deprived for a large majority of cancer sites, with no significant inverse association . Our findings are therefore supported by those from the literature, and bring new information about the situation in France and the impact of social deprivation on cancer survival for cancer sites with mitigated results in the literature (such as stomach, ovary, melanoma, thyroid, CNS or pancreas).…”
Section: Discussionsupporting
confidence: 85%
“…The lower survival found among patients living in the most deprived areas compared to those living in the least deprived ones regarding colon‐rectum cancer, breast cancer and cervical cancer might result from inequalities in cancer screening uptake, which have been identified in several French studies . Additionally, disparities in stage at diagnosis and therapeutic management according to deprivation have been related to cancer survival inequalities in previous research . However, neither stage at diagnosis nor patients’ treatment history were available in the cancer registries data used for our study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…1,2 The majority of studies that have investigated the association between area of residence and cancer survival were conducted in high-income countries, but the findings have been inconsistent. [3][4][5][6][7][8] Furthermore, the potential roles of stage at cancer diagnosis, comorbidity, treatment, and health-related lifestyle factors in rural/urban differences in cancer outcomes have not been fully explored. A review conducted in 1992 of patterns of cancer mortality and survival in rural and urban regions suggested that residents of rural areas were more likely to be diagnosed at advanced stage compared with those living in urban communities.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, both socioeconomic and geographic differences in cancer survival have been demonstrated. 2,3 At the same time, the close relationship between the social determinants of health and migration raises concerns about the health of the immigrant population. 4 In 2017, immigrants constituted 14% of the Norwegian population.…”
mentioning
confidence: 99%